Chairperson Leadership Paradigm and Its Flaws - Harsono, Ari (UI Scholars Hub, 2010)
Leadership which has been well-known and applied in times is actually a manifestation of paradigm of ‘the chairperson leadership’ or ‘person leadership’. Research shows that this paradigm implies several of weaknesses which the organizations themselves are less aware of. This weaknesses have made and will cause many losses, such as crisis in personality, social humanity, economy, culture, and environment. The fundamental weakness –linked to others– is the person centered characteristic which empowers the chairperson to be the last one to judge in decision making.